Analysis and Implementation of the Occupational Safety and Health Program Behavior K3 Culture on Projects Construction and Performance at PT.X - Annisa Agustina; Kholil Kholil; Soehatman Ramli (Dinasti International Journal of Education Management And Social Science, 2024)
Management source Power Man is something that must be noticed by the company. A number of necessary things that need more attention are safety and health for employees at work. Johnson et al. (2014) in Newnam and Muir (2019) stated if culture about work safety has gotten attention during a number of last year. Attention to work safety is influenced by several factors, namely: existing changes have an impact on understanding the environment, along with formation attitudes and values. In Indonesia itself, awareness about the importance of safety and health in the work environment already gets attention from the government. This is demonstrated by the existing regulation regarding regulated K3 in Constitution Number 1 of 1970. From the various explanations above, yes, as seen Implementation culture, safety, and health in the workplace (K3) are things that must be done by all companies in Indonesia. Therefore, this research was conducted to address research gaps previously identified by Umeokafor (2018). For the implementation of K3 in Ghana, see Lee et al. (2020), which was carried out for the implementation of K3 in South Korea, and Almazrouei (2019) for the implementation of K3 in the oil and gas industry in Saudi Arabia. Where is the third study done using the qualitative method? This research will be about the implementation K3 culture at PT. X, which is a garment company located in Semarang. This research is a quantitative study done with a method of spreading a questionnaire to PT employees. X with a minimum of one term of service know for see is K3 culture already held with both at PT. X.